Platinum surface modification with cerium species and the effect against the methanol anodic reaction - Bonilla, S. H.; Carvalho, J. G. A. [UNESP]; Almeida, C. M. V. B.; Giannetti, B. F.; Zinola, C. F. (Elsevier B.V. Sa, 2008)
Spontaneous deposition and electrochemical deposition by potential perturbation programs were used to place cerium-containing species on platinum surfaces in acid solution. Cyclic voltammetric profiles of cerium-modified platinum surfaces obtained after potentiostatic or potentiodynamic procedures (applied in the true hydrogen evolution region) differ from those recorded after spontaneous methods. However, the catalytic effects are nearly the same on these cerium-modified platinum surfaces for methanol electrooxidation, i.e. lower onset potential values for the anodic reaction. Besides, a different electrocatalytic effect was observed at large positive potentials on methanol oxidation due to the cerium oxide capability of oxygen storage. This effect is observed on platinum modified by a drastic potentiostatic procedure (by applying -2.0 V) in cerium(IV) acid solution. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: cerium; platinum; methanol; fuel cells; deposition